Wee1 Inhibition by MK-1775 Leads to Tumor Inhibition and Enhances Efficacy of Gemcitabine in Human Sarcomas - Kreahling, Jenny M. (Public Library of Science, 2013)
Sarcomas are rare and heterogeneous mesenchymal tumors affecting both pediatric and adult populations with more than 70 recognized histologies. Doxorubicin and ifosfamide have been the main course of therapy for treatment of sarcomas; however, the response rate to these therapies is about 10–20% in metastatic setting. Toxicity with the drug combination is high, response rates remain low, and improvement in overall survival, especially in the metastatic disease, remains negligible and new agents are needed. Wee1 is a critical component of the G2/M cell cycle checkpoint control and mediates cell cycle arrest by regulating the phosphorylation of CDC2. Inhibition of Wee1 by MK1775 has been reported to enhance the cytotoxic effect of DNA damaging agents in different types of carcinomas. In this study we investigated the therapeutic efficacy of MK1775 in various sarcoma cell lines, patient-derived tumor explants ex vivo and in vivo both alone and in combination with gemcitabine, which is frequently used in the treatment of sarcomas. Our data demonstrate that MK1775 treatment as a single agent at clinically relevant concentrations leads to unscheduled entry into mitosis and initiation of apoptotic cell death in all sarcomas tested. Additionally, MK1775 significantly enhances the cytotoxic effect of gemcitabine in sarcoma cells lines with different p53 mutational status. In patient-derived bone and soft tissue sarcoma samples we showed that MK1775 alone and in combination with gemcitabine causes significant apoptotic cell death. Magnetic resonance imaging (MRI) and histopathologic studies showed that MK1775 induces significant cell death and terminal differentiation in a patient-derived xenograft mouse model of osteosarcoma in vivo. Our results together with the high safety profile of MK1775 strongly suggest that this drug can be used as a potential therapeutic agent in the treatment of both adult as well as pediatric sarcoma patients.